Influence of a New Media Data Interaction System on the Course Teaching Effect - Ke, Wenjuan; Ji, Zijun (International Journal of Emerging Technologies in Learning (iJET), 2023)
The new media data interaction system is the product of the joint development of information technology, computer technology, and education reform, which has a certain impact on the traditional teaching model. To continuously improve the course teaching effect, the influence of the new system on the course teaching effect was investigated. Experimental and control classes were set and the number of each class and teaching time were confirmed. The experimental class adopted the new media data interaction system to assist the course teaching and made courseware of such a system through different methods, such as literature data, questionnaires, and experiment methods. Moreover, a pretest questionnaire and an in-class observation scale were designed and the experimental data were analyzed through t-test and statistical analysis. Results indicate there is no significant difference in student ability and academic performance between the experimental and control classes before participating in the study. After the participation, the mean scores of the in-class scale in the learning interest, learning attitude, and communication ability of the experimental class are 13.42, 13.26, and 16.37, respectively, which are significantly different from those of the conventional class (p<0.05). Thus, the new media data interaction system can improve the course teaching effect.